Potential risk of heavy metals release in sediments and soils of the Yellow River Basin (Henan section): A perspective on bioavailability and bioaccessibility - Peng Wang; Furong Yu; Haonan Lv; Lin Wu; Hui Zhou (Ecotoxicology and Environmental Safety)
The ecology of watersheds plays an important role in regulating regional climate and human activities. The sediment-soil system in the middle and lower reaches of the Yellow River Basin (Henan section) was explored. The spatial distribution characteristics of heavy metals (HMs) showed that tributaries, which are affected by anthropogenic activities, contain higher concentrations of HMs than the main channel. Sequential extraction experiments indicated that Cd had the strongest potential to be released, followed by Mn. In vitro simulation experiments showed that gastric and pulmonary fluids rendered these two orders of magnitude more bioaccessible compared to sweat. Moreover, Cd exhibited the highest bioaccessibility in both gastric and lung fluids. When bioaccessibility was considered in the evaluation of health risks, more than 82 % of reductions in non-carcinogenic and carcinogenic risk indices were observed in children and adults. A positive matrix factorization model was utilized to determine the potential sources of HMs: industrial sources, natural sources, and mixed agricultural and transportation sources were identified as the three main sources of HMs in sediments and soils. In addition, mining activities were also an HMs source in sediments.